Dental plaque regrowth studies to evaluate chewing gum formulations incorporating magnolia bark extract. (October 2017) - Komarov, Gleb N.; Hope, Christopher K.; Wang, Qian; Adejemi, Adejumoke A.; Smith, Philip W.; Burnside, Girvan; Inui, Taichi; Higham, Susan M.
Highlights: Magnolia bark extract has antimicrobial properties that could inhibit dental plaque. Chewing gums containing magnolia bark extract were assessed in volunteers. Gum incorporating magnolia bark extract and a surfactant reduced plaque regrowth. Magnolia bark gum may contribute towards improvements in oral health. Abstract: The plaque inhibiting properties of magnolia bark extract (MBE) were assessed in a volunteer trial following the consumption of various sugar-free chewing gum formulations over a period of 4-days. Paired t-tests demonstrated significant (p < 0.15) differences between the placebo and a gum containing MBE (0.4%) plus lauramide arginine ethyl ester (LAE) (0.5%) with respect to% plaque coverage (36.3% vs 34.0%) and area of plaque fluorescence (109.4 mm 2 vs 75.2 mm 2 ). These findings were supported by microbiological counts of total salivary bacteria (7.77 log10 cfu/ml vs 7.45 log10 cfu/ml) as well as Streptococcus spp. (6.76 log10 cfu/ml vs 6.29 log10 cfu/ml). MBE (0.4%) + LAE (0.5%) delivered by chewing gum had a moderate inhibitory effect on plaque formation and salivary bacteria. Limiting the formation of dental plaque and salivary bacteria, specifically oral streptococci, could contribute towards an improvement in oral health with respect to gum disease and caries.